Few mitochondrial DNA sequences are inserted into the turkey (Meleagris gallopavo) nuclear genome: evolutionary analyses and informativity in the domestic lineage. (9th March 2018) - Schiavo, G.; Strillacci, M. G.; Ribani, A.; Bovo, S.; Roman‐Ponce, S. I.; Cerolini, S.; Bertolini, F.; Bagnato, A.; Fontanesi, L.
Summary: Mitochondrial DNA (mtDNA) insertions have been detected in the nuclear genome of many eukaryotes. These sequences are pseudogenes originated by horizontal transfer of mtDNA fragments into the nuclear genome, producing nuclear DNA sequences of mitochondrial origin (numt). In this study we determined the frequency and distribution of mtDNA‐originated pseudogenes in the turkey ( Meleagris gallopavo ) nuclear genome. The turkey reference genome (Turkey_2.01) was aligned with the reference linearized mtDNA sequence usinglast . A total of 32 numt sequences (corresponding to 18 numt regions derived by unique insertional events) were identified in the turkey nuclear genome (size ranging from 66 to 1415 bp; identity against the modern turkey mtDNA corresponding region ranging from 62% to 100%). Numts were distributed in nine chromosomes and in one scaffold. They derived from parts of 10 mtDNA protein‐coding genes, ribosomal genes, the control region and 10 tRNA genes. Seven numt regions reported in the turkey genome were identified in orthologues positions in the Gallus gallus genome and therefore were present in the ancestral genome that in the Cretaceous originated the lineages of the modern crown Galliformes. Five recently integrated turkey numts were validated by PCR in 168 turkeys of six different domestic populations. None of the analysed numts were polymorphic (i.e. absence of the inserted sequence, as reported in numts of recent integration in other species), suggesting that the reticulate speciation model is not useful for explaining the origin of the domesticated turkey lineage.